A Multidimensional Approach to Post-Traumatic Stress Disorder from Theory to Practice - El-Baalbaki, Ghassan; Fortin, Christophe (IntechOpen, 2016)
Is the heart rate variability biofeedback a promising intervention for PTSD? Is there a link between early traumatic events in life and the presence of psychopathology and interpersonal difficulties in adulthood? Wondering what is the next step for humanistic, psychodynamic, or CBT therapists working with PTSD patients? Look no further. A Multidimensional Approach to Post-Traumatic Stress Disorder - From Theory to Practice explores the PTSD through the lens of the biopsychosocial model. The various topics covered in this book - from the neuro-bio-physiological aspects to the clinical and methodological dimensions involved in investigating the PTSD - address a wide variety of concerns regarding the disorder. The authors of the chapters are internationally renowned leaders in their field of science, sharing both the results of their latest investigations and their thoughtful perspectives on future fundamental and clinical research on PTSD. The knowledge shared by the authors results in an engaging and scientific experience for the initiated reader, yet accessible to the newcomers who are just learning about PTSD.